2004
DOI: 10.1124/jpet.104.071720
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Mast Cells in Adenosine-Mediated Bronchoconstriction and Inflammation in an Allergic Mouse Model

Abstract: In allergen-induced asthma, activation of lung mast cells leads to bronchial constriction, increased mucus secretion, and an increase in the localization of inflammatory cells to the airways. The purpose of this study was to explore the role of mast cells in adenosine-mediated airway reactivity and inflammation using the mast cell degranulating agent, compound 48/80 (C48/80). Mice were sensitized and challenged with ragweed (or 0.9% saline) followed by C48/80 administration twice a day in increasing doses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Whole body plethysmography has been used previously to determine the extent of airway hyperresponsiveness and as a measure of airway obstruction (12,17,18,45). We used this method to determine the differences between A 1 WT and A 1 KO responses to MCh and NECA.…”
Section: Discussionmentioning
confidence: 99%
“…Whole body plethysmography has been used previously to determine the extent of airway hyperresponsiveness and as a measure of airway obstruction (12,17,18,45). We used this method to determine the differences between A 1 WT and A 1 KO responses to MCh and NECA.…”
Section: Discussionmentioning
confidence: 99%
“…In other mouse allergy models, A 2B receptors were identified as the main receptor subtype involved in increases in ion transport (Kornerup et al, 2005;Mustafa et al, 2007). Mast cells were shown to be involved in adenosine-mediated bronchoconstriction and inflammation in an allergic mouse model (Oldenburg and Mustafa, 2005). Mast cells were claimed to be activated after adenosine challenge in allergic, but not nonallergic, patients with asthma (Bochenek et al, 2008).…”
Section: A Asthmamentioning
confidence: 99%
“…On day 14, mice were challenged with NECA, AMP, or allergen, and the airway reactivity was measured using barometric plethysmography Mustafa, 2002, 2006;Oldenburg and Mustafa, 2005). It has been previously shown that changes (increases or decreases) in Penh correlate with changes (increases or decreases) in airway resistance in this model (Justice et al, 2001).…”
Section: Experimental Protocolsmentioning
confidence: 99%